Komunikasi Interpersonal dan Representasi Identitas Lokal dalam Serial When Life Gives You Tangerines: - Namira Jasmine Aiswari; Alya Attalya; Vivianne Verna Yedija; Alysha Amanda Adityaputri; Arsih Amalia Chandra Permata5; Wiyata Wiyata (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
This study investigates how the Korean television series When Life Gives You Tangerines (2025) depicts the local identity of Jeju Island. The research analyzes dialogue, scenes, and visuals that portray interpersonal communication among characters and Jeju culture using a descriptive qualitative approach with content analysis. The findings show that local values can be transmitted through interpersonal communication via Jeju dialect and calm communication style. Jeju Island is portrayed as a living identity rather than merely a backdrop, the series positions Jeju as a meaningful cultural destination, landscapes and artifacts strengthen cultural identity, and the narrative emphasizes authenticity. Additionally, the series conveys messages of Korean cultural preservation through the depiction of 1950s traditions.